Thinker, Soldier, Scribe: cross-sectional study of researchers' roles and author order in the Annals of Internal Medicine. Issue 6 (24th June 2017) - Perneger, Thomas V; Poncet, Antoine; Carpentier, Marc; Agoritsas, Thomas; Combescure, Christophe; Gayet-Ageron, Angèle
Abstract : Objective: How researchers' contributions relate to author order on the byline remains unclear. We sought to identify researchers' contributions associated with author order, and to explore the existence of author profiles. Design: Observational study. Setting: Published record. Participants: 1139 authors of 119 research articles published in 2015 in the Annals of Internal Medicine . Primary outcomes: Presence or absence of 10 contributions, reported by each author, published in the journal. Results: On average, first authors reported 7.1 contributions, second authors 5.2, middle authors 4.0, penultimate authors 4.5 and last authors 6.4 (p<0.001). The first author made the greatest contributions to drafting the article, designing the study, analysing and interpreting the data, and providing study materials or patients. The second author contributed to data analysis as well and to drafting the article. The last author was most involved in obtaining the funding, critically revising the article, designing the study and providing support. Factor analysis yielded three author profiles— Thinker (study design, revision of article, obtaining funding), Soldier (providing material or patients, providing administrative and logistical support, collecting data) and Scribe (analysis and interpretation of data, drafting the article, statistical expertise). These profiles do not strictly correspond to byline position. Conclusions: First, second and last authors of research articles made distinct contributions to published research. Three authorship profiles can be used to summarise author contributions. These findings shed light on the organisation of clinical research teams and may help researchers discuss, plan and report authorship in a more transparent way.